Nanogap‐Engineerable Electromechanical System for Ultralow Power Memory. Issue 2 (3rd December 2017) - Zhang, Jian; Deng, Ya; Hu, Xiao; Nshimiyimana, Jean Pierre; Liu, Siyu; Chi, Xiannian; Wu, Pei; Dong, Fengliang; Chen, Peipei; Chu, Weiguo; Zhou, Haiqing; Sun, Lianfeng
Abstract: Nanogap engineering of low‐dimensional nanomaterials has received considerable interest in a variety of fields, ranging from molecular electronics to memories. Creating nanogaps at a certain position is of vital importance for the repeatable fabrication of the devices. Here, a rational design of nonvolatile memories based on sub‐5 nm nanogaped single‐walled carbon nanotubes (SWNTs) via the electromechanical motion is reported. The nanogaps are readily realized by electroburning in a partially suspended SWNT device with nanoscale region. The SWNT memory devices are applicable for both metallic and semiconducting SWNTs, resolving the challenge of separation of semiconducting SWNTs from metallic ones. Meanwhile, the memory devices exhibit excellent performance: ultralow writing energy (4.1 × 10 −19 J bit −1 ), ON/OFF ratio of 10 5, stable switching ON operations, and over 30 h retention time in ambient conditions. Abstract : A novel design of nonvolatile memory device based on sub‐5 nm nanogaped single‐walled carbon nanotubes (SWNTs) via the electromechanical motion is demonstrated. The nanogaps are readily realized by electroburning in a partially suspended SWNT device with a nanoscale region. The memory devices have ultralow power consumption and exhibit excellent performance in ambient conditions.